U.S public reactions to the first Chinese immigration wave in California in the second half of the nineteen century = Phản ứng của công chúng Mỹ với làn sóng người Trung Quốc nhập cư ở California nửa sau thế kỷ XIX - Nguyễn, Thanh Thủy (2020)
As a nation of immigrants admitting more than 50 newcomers since its early day, the United States has always been a subject of debates and discussions. It comes down to the fact that different ethnic immigrant groups bring different language, religion and culture to the New World. Therefore, the question that has constantly been addressed is the assimilation of immigrant groups into American mainstream society. Looking back at the U.S history with a massive influx of Chinese immigrants in 1850, the matter will somehow be delivered. Like other immigrant groups, many poor Chinese under Manchu Rule decided to venture to the New World for wealth, land and freedom. The favorite issue that attracts most attention from readers is question about U.S public reactions to this ethnic group, who had never got access to Western civilization. As subsequently be presented in this paper, there are some dominant factors in U.S public reactions to Chinese in California: racial differences, job competition with the whites, economic depression in 1870, practice of opium smoking and prostitution. After that, U.S public reactions to Chinese immigrants in California, the state that contained the largest Chinese population in U.S, will be revealed. Overall, the first Chinese wave of immigration has such influence on U.S society in general and California in particular. Nevertheless, Chinese labor, to a certain extent, changed the appearance of the American West in the second half of the nineteenth century